Pengaruh Media Diorama Terhadap Hasil Belajar IPA Di SD Negeri 73 Buton - Fitriani. B (Departement of Mathematics Education, 2023)
This research aims to determine the effect of diorama media on student learning outcomes in science lessons on the water cycle in class V at SD Negeri 73 Buton. This type of research used quantitative research. Pre-experimental research design: One Group Pretest-Posttest Design. The approach uses a quantitative pretest and posttest type approach. The samples in this research were all students in class V of SDN 73 Buton with a total of 18 students. Data collection was carried out using a test in the form of answer choices with a total of 15 questions. The results of the research obtained a mean pretest score of 46.40 and a mean posttest score of 71.93, which shows the difference in the learning process without treatment and learning that was given treatment. Based on data obtained using SPSS Statistics software, a significance result (2-tailed) was obtained of 0.002 < 0.05. From the results obtained, decisions are made, namely accepted and rejected. So it can be decided that there is an influence of diorama media on student learning outcomes in the water cycle material in class V at SDN 73 Buton. This shows that the media has an equal impact in increasing students' understanding of the water cycle material. These findings provide valuable guidance to educators to be creative in the teaching and learning process.